The Impact of Electric Vehicles in an Unbalanced Distribution Network with Renewables - Demetriou, Victoria (My University, 2022)
The continuous rise of Greenhouse Gases (GHG) has set the established goals of climate neutrality into an accelerative mode. Rigorous transition into cleaner and greener energy is a must. Starting with the electrification of the transportation sector, which is eminent for this energy transition. Consequently, the spotlight is on the integration and wider commercialization of electric vehicles. In order for the transition to be successful effective and accurate research has to be further developed regarding this matter and its possible negative effects on the power grid. With this in mind, the thesis covers the topic of the impact of electric vehicles in the distribution network with penetration of renewable energies. Different models of variable parameters such as driver behavior, charger capabilities, and photovoltaic generation have been simulated via an algorithm to observe the differences in sensitivity in the behavior of the distribution network after each proposed scenario. The two scenarios include, a fixed residential load with EV penetration with and without the utilization of residential photovoltaic loads. The Monte-Carlo method is used in order to account for the variability in the simulated models.
Keywords: Εlectric vehicles; Renewable energy sources; LV distribution network; Charging profiles; Monte-Carlo simulation; Ηλεκτρικά οχήματα; Ανανεώσιμες πηγές ενέργειας; Δίκτυο διανομής